(untitled) (Bioscience Journal, 2023)
The effects of systemic insulin administration at different concentrations on the testicular tissue of diabetic adult rats, induced by streptozotocin, are evaluated by the morphological analysis of spermatogenic process. Twenty-four adult male rats were divided into 1) Control Group: they received citrate buffer, by intraperitoneal injection; 2) Diabetic Group: induced by intraperitoneal injection of streptozotocin (60 mg. kg-1 of body weight); 3) Insulin 50%: induced diabetes treated with half of standard dosage of insulin; 4) Insulin 100%: induced diabetes treated with standard dose of insulin. After eight weeks, animals were weighted and anesthetized; testicles were removed and processed in resin. Body and testicular weight of diabetic rats decreased when compared to that of control. Parameters increased with insulin therapy. Testosterone levels were low in diabetic animals but rates recovered after insulin therapy. Nuclear diameter and volume of Leydig cells decreased in diabetic rats although they significantly increased after insulin therapy. Results showed that the administration of insulin in diabetic rats promoted a protective effect of testicular parenchyma, enhancing efficient recovery on testosterone levels and increase in daily sperm production.